2021
DOI: 10.3390/jimaging7010010
|View full text |Cite
|
Sign up to set email alerts
|

Improved Acquisition and Reconstruction for Wavelength-Resolved Neutron Tomography

Abstract: Wavelength-resolved neutron tomography (WRNT) is an emerging technique for characterizing samples relevant to the materials sciences in 3D. WRNT studies can be carried out at beam lines in spallation neutron or reactor-based user facilities. Because of the limited availability of experimental time, potential imperfections in the neutron source, or constraints placed on the acquisition time by the type of sample, the data can be extremely noisy resulting in tomographic reconstructions with significant artifacts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Energy-resolved Neutron Imaging has developed in recent years owing to the use of bright pulsed neutron beamline facilities at neutron spallation sources and is applied to study the composition, strain, and texture of the sample as a function of the spatial resolution [ 62 , 63 , 64 ]. Because the data are affected by noise, Machine Learning could be successfully applied to cultural heritage optimizing the acquisition time and improving the quantification results.…”
Section: Deep Learning Applicationsmentioning
confidence: 99%
“…Energy-resolved Neutron Imaging has developed in recent years owing to the use of bright pulsed neutron beamline facilities at neutron spallation sources and is applied to study the composition, strain, and texture of the sample as a function of the spatial resolution [ 62 , 63 , 64 ]. Because the data are affected by noise, Machine Learning could be successfully applied to cultural heritage optimizing the acquisition time and improving the quantification results.…”
Section: Deep Learning Applicationsmentioning
confidence: 99%
“…For example, it is common across SCT applications to use detectors which are approximately 2000 × 2000 pixels, and corresponding CT reconstructions to have sizes of the order of 2000 × 2000 × 2000 voxels. In the case of hyper-spectral SCT instruments [11],…”
Section: Limited-angle Measurementsmentioning
confidence: 99%
“…4DCT is used to study dynamic phenomena such as solidification [41], phase transformations [42], crack formation [43], and battery degradation [44]- [46]. 4DCT is performed using a variety of radiation sources that include X-rays [44], electrons [47], and neutrons [48], [49] at resolutions ranging from nanometer to micron length scales mostly using the set-up of the type in Fig. 1 (a).…”
Section: Mbir Volume Rendering Fbp (Analytic Reconstruction) Mbirmentioning
confidence: 99%
“…In order to address the challenges of long scan times and limited user feedback, advanced scanning protocols based on the golden ratio method 29 combined with model-based iterative reconstruction (MBIR) algorithms have recently been proposed 30 by our team. It was demonstrated that by streaming data to a powerful compute node, and using a fast implementation of MBIR 31 , it was possible to reconstruct CT scans with high image quality while performing an experiment, thereby paving the way to make real-time decision during an experiment.…”
Section: Introductionmentioning
confidence: 99%